Sistem Rekrutmen Kepala Sekolah Menurut Permendiknas: Sebuah Pengantar - Acep Mulyadi (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2012)
In the planning and execution of school program, the head of the institution, teacher’s students and their parents have all to join hands to attain common goals and purposes. On him the proper working of school ultimately depends. The reputation of the school and the position that it holds in the society depends in a large measure on the influence that he exercises over his colleagues his pupils and general public. True, on his ability and skill, as a sound and effective educational leader depends the success of a school system. Headmaster is the leader and the centre of the whole organization of the school. This article describes that headmaster must have several competences. Permendiknas Number 16/ 2007 obliged headmaster and teacher have four competences; pedagogical competence, personal competence, social competence and professional competence. The result of the research that the recruitment model according to kepmendiknas 296/U/1996, Permendiknas 0162/U/2003 and Permendiknas no. 28/2010. There are still some weaknesses that are not yet showing up the fair principles for headmaster/the teachers having fulfilled the general recruitments and specific recruitments for only one teacher from each school asked to be a candidate. The tree rules organize their recruitment that is about faith and belief to the only God and there is no exact measure tool so that is must be made measure tool that can be valued through observation. Faith and belief are the main keys for an official in doing his duty. It is needed to be added that family condition must be filled in as recruitment for selection, because the family condition badly influence the professionalism of the official. The selection model at regency level conducted by third side, it is objectiveness of the result has to be kept or the purity of test results in deciding the graduation. By the strength and weakness, it needs to reveal up the ideal and objective school principal recruitment model